Progress or Pathology? Differential Diagnosis and Intervention Criteria for Meditation-Related Challenges: Perspectives From Buddhist Meditation Teachers and Practitioners - Lindahl, Jared R.; Cooper, David J.; Fisher, Nathan E.; Kirmayer, Laurence J.; Britton, Willoughby B. (Frontiers in Psychology, 2020)
Studies in the psychology and phenomenology of religious experience have long acknowledged similarities with various forms of psychopathology. Consequently, it has been important for religious practitioners and mental health professionals to establish criteria by which religious, spiritual, or mystical experiences can be differentiated from psychopathological experiences. Many previous attempts at differential diagnosis have been based on textual accounts of mystical experience or on outdated theoretical studies of mysticism. In contrast, this study presents qualitative data from contemporary Buddhist meditation practitioners and teachers to identify salient features that can be used to guide differential diagnosis. The use of certain existing criteria is complicated by Buddhist worldviews that some difficult or distressing experiences may be expected as a part of progress on the contemplative path. This paper argues that it is important to expand the framework for assessment in both scholarly and clinical contexts to include not only criteria for determining normative fit with religious experience or with psychopathology, but also for determining need for intervention, whether religious or clinical. Qualitative data from Buddhist communities shows that there is a wider range of experiences that are evaluated as potentially warranting intervention than has previously been discussed. Decision making around these experiences often takes into account contextual factors when determining appraisals or need for intervention. This is in line with person-centered approaches in mental health care that emphasize the importance of considering the interpersonal and cultural dynamics that inevitably constitute the context in which experiences are evaluated and rendered meaningful.